Variants Affecting the C-Terminal of CSF1R Cause Congenital Vertebral Malformation Through a Gain-of-Function Mechanism - Liu, Bowen; Zhao, Sen; Yan, Zihui; Zhao, Lina; Lin, Jiachen; Wang, Shengru; Niu, Yuchen; Li, Xiaoxin; Qiu, Guixing; , Deciphering Disorders Involving Scoliosis and COmorbidities (DISCO) study; Zhang, Terry Jianguo; Wu, Zhihong; et al. (Frontiers in Cell and Developmental Biology, 2021)
CSF1R encodes the receptor of Colony Stimulating Factor 1 Receptor which participates in regulation of proliferation, differentiation and biological activity of monocyte/macrophage lineage. Pathogenic variants in CSF1R could lead to autosomal dominant adult-onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) or autosomal recessive skeletal dysplasia. In this study, we identified three heterozygous deleterious rare variants of CSF1R from a congenital vertebral malformation (CVM) cohort. All those variants are located within carboxy-terminal region of CSF1R protein and proved to increase the stability of protein, which was confirmed by immunoblotting. In vivo, we established zebrafish CSF1R overexpression model, which exhibit CVM phenotypes such as hemivertebra and vertebra fusion. Furthermore, injection of mutated CSF1R mRNA without carboxy-terminus led to a higher proportion of zebrafish with vertebral malformations than wild-type CSF1R mRNA did (p= 0.03452), indicating a gain-of-function effect of variants in carboxy-terminal region of CSF1R. In conclusion, variants affecting C-terminal of CSF1R could cause CVM though a gain-of-function mechanism.